Making Public Policy: The New Philanthropists and American Education. - Rogers, Robin (American Journal of Economics & Sociology, 2015)
Power in K-12 education is rapidly moving from local school boards and government to extraordinarily wealthy private philanthropists. Building networks among nonprofits, government agencies, school districts, and others, private foundations such as the Gates, Broad, and Walton family foundations are fundamentally restructuring American K-12 education. The Common Core State Standards, teacher evaluation, and charter schools are a few of the initiatives these funders are backing. The massive influx of private money into education policy and its influence over public education raises questions around the proper role of philanthropy in a democracy. In a society with increasing wealth inequality, should the economic elite be able to gain further power to shape social institutions through giving? Are there or should there be any limits to this power? Examining specific trends and events in education philanthropy over the last 10 years, this article identifies key players in philanthropic education reform and argues that philanthropy in education is now playing a policy-making role-without checks and balances-that is qualitatively and quantitatively different than before. I conclude with a cautionary note on the dangers of letting education policy become the domain of the economic elite.